The different trends in the burden of neurological and mental disorders following dietary transition in China, the USA, and the world: An extension analysis for the Global Burden of Disease Study 2019 - Liang, Shan; Wang, Li; Wu, Xiaoli; Hu, Xu; Wang, Tao; Jin, Feng (Frontiers in Nutrition, 2023)
The highly processed western diet is substituting the low processed traditional diet in the last decades globally. Increasing research found that diet with poor quality like western diet disrupted gut microbiota and increased the susceptibility of various neurological and mental disorders, while balanced diet regulated gut microbiota, prevent, and alleviate the neurological and mental disorders. Yet few research studied the association between the disease burden expanding of neurological and mental disorders with dietary transition. We compared the disability-adjusted life-years (DALYs) trend by age for neurological and mental disorders in China, USA, and Global from 1990 to 2019, evaluated the dietary transition in the past 60 years, and analyzed the association between the burden trend of the two disorders with the changes in diet composition and food production. We identified age-related upward pattern in disease burden in China. Compared with USA and Global, the Chinese neurological and mental disorders DALYs percent was least in generation over 75, but quickly increased in younger generation and surpassed Global or/and USA in the last decades. The age-related upward pattern in Chinese disease burdens had not only shown in cardiovascular diseases, neoplasms, and diabetes mellitus, but also appeared in depressive disorders, Parkinson’s disease, Alzheimer’s disease and other dementias, schizophrenia, headache disorders, anxiety disorders, conduct disorders, autism spectrum disorders, and eating disorders, successively. And the upward trend was associated with the dramatic dietary transition including reduction in dietary quality and food production sustainability, during which the younger generation are more affected than the older. Following the increase in total calorie intake, alcohol intake, ratios of animal to vegetal foods, and poultry meat to pulses, the burdens of the above diseases continuously rose. Even the usages of pesticides were positively correlated with the burdens of Parkinson’s disease, schizophrenia, cardiovascular diseases, and neoplasms. Contrary to China, the corresponding burdens of USA trended to reduce with the improvements in diet quality and food production sustainability. Our results suggest that improving diet quality and food production sustainability might be a promising way to stop the expanding burdens of neurological and mental disorders.